Street Culture and Gun Violence: Exploring the Reputation–Victimization Paradox - Dierenfeldt, Rick (Journal of interpersonal violence, 2021)
Anderson’s thesis of a code of the street has been broadly applied to the study of violence, but race- and gender-specific multilevel analyses of gun violence are scant within the literature. An unresolved debate also surrounds the link between violent victimization and adherence to street culture; underscored by an apparent reputation–victimization paradox among those who engage in street behaviors. The current study contributes to the literature by assessing the direct influence of incident setting and victim–offender familiarity on the likelihood of gun use by Black males in the course of aggravated assaults; and the degree to which the confluence of these factors is conditioned by levels of disadvantage and violence in the community. To accomplish this, we apply hierarchical generalized linear modeling to incident-level data from the National Incident-Based Reporting System in conjunction with contextual-level data from the counties in which the incidents are nested. Our findings suggest victim–offender familiarity and public settings are negatively associated with gun violence and the confluence of these factors further reduces the probability of gun use. This relationship, however, is conditioned by levels of disadvantage and violence in the community, providing preliminary evidence of both the violence increasing and decreasing effects of street culture hypothesized by Anderson.